Understanding Photoinduced Symmetry- Breaking Charge Separation - Johannes Wega (CHIMIA)
Symmetry-breaking charge separation (SB-CS) is a photoinduced electron transfer reaction in which the chromophore acts as both the acceptor and the donor. This reaction which is still poorly understood may enable long-lived charge separation interesting for many applications. Here we show that SB-CS can be realised bimolecularly with perylene and discuss the factors favouring it. Furthermore, using a pyrene bichromophoric system, we discuss the influence of interchromophore coupling and how the photophysics can be fine-tuned to yield SB-CS over other processes such as excimer formation.